2013
DOI: 10.1002/pc.22523
|View full text |Cite
|
Sign up to set email alerts
|

Non-fickian three-dimensional hindered moisture absorption in polymeric composites: Model development and validation

Abstract: A new, three‐dimensional, anisotropic non‐Fickian diffusion model is developed to characterize moisture absorption in polymeric composites. The new hindered diffusion model extends the classical Fickian theory to include the effects of the interaction of diffusing molecules with the chemical and physical structure of polymeric composites. The numerical solution of the hindered diffusion model is obtained for a three‐dimensional, anisotropic domain by using a forward‐time, centered‐space finite difference techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 72 publications
0
26
0
Order By: Relevance
“…It has been shown that most often polymer composites follow a Fickian diffusion process . However, for explaining mechanisms behind non‐Fickian behavior other models can be used . Different methods of measuring water uptake are investigated on laminates and in order to define the diffusion coefficient moisture uptake studies in glass fiber/epoxy composites have been carried out.…”
Section: Methodsmentioning
confidence: 99%
“…It has been shown that most often polymer composites follow a Fickian diffusion process . However, for explaining mechanisms behind non‐Fickian behavior other models can be used . Different methods of measuring water uptake are investigated on laminates and in order to define the diffusion coefficient moisture uptake studies in glass fiber/epoxy composites have been carried out.…”
Section: Methodsmentioning
confidence: 99%
“…; Helbling and Karbhari; LaPlante et al ; Grace and Altan). In the Langmuir model, the macroscopic sorption is modeled by two stages, consisting of a Fickian diffusion‐dominated stage and a relaxation‐dominated stage, where fluid molecules interact with the macromolecular structure of the polymer.…”
Section: Introductionmentioning
confidence: 99%
“…This interaction of processes is categorized as "anomalous diffusion behavior." Many of the above studies consider empirical and ad-hoc models to describe the non-Fickian diffusion process in polymers, for example the so-called Langmuir model (Carter and Kibler 6 ; Lee and Peppas 10 ; Perreux and Suri 11 ; Popineau et al 12 ; Helbling and Karbhari 13 ; LaPlante et al 14 ; La Saponara 15 ; Grace and Altan 16 ). In the Langmuir model, the macroscopic sorption is modeled by two stages, consisting of a Fickian diffusion-dominated stage and a relaxation-dominated stage, where fluid molecules interact with the macromolecular structure of the polymer.…”
Section: Introductionmentioning
confidence: 99%
“…The methods to recover the absorption parameters as well as the utility and accuracy of the HDM has been investigated in recent publications [15,16]. The governing equations for the three-dimensional, anisotropic hindered diffusion model can be expressed as,…”
Section: Moisture Absorption Modelsmentioning
confidence: 99%